Tailoring the surface reactivity of silicon surfaces by partial halogenation - Soria, Federico Ariel (2013)
Density functional theory was used to investigate the reactivity of partially chlorinated and stepped silicon surfaces with molecules having N, O, and S head groups in relation to the development of selectively functionalized surfaces. The activation energy barriers for the formation of Si–N, Si–O, and Si–S bonds by breakage of the Si–Cl bond are very sensitive to steric factors and this fact can be used to tune the surface reactivity. Whereas the fully chlorinated Si(111) surface has high energy barriers in the range 34–64 kcal/mol for the reactions with NH3, H2O, H2S, CH3NH2, CH3OH, and CH3SH molecules, the partially chlorinated surface has much lower barriers in the range 13–34 kcal/mol, indicating that some molecules may react at almost room temperature with the SiCl groups. The reactions of these molecules on SiH groups have high energy barriers for all surfaces (in the range 33–42 kcal/mol) indicating that they form a matrix of unreactive groups around the reactive SiCl sites. Unlike the fully chlorinated Si(111) surface, the SiCl groups on the reconstructed step edges are very reactive, showing the lowest activation energy barriers. The different reactivities of SiCl groups on the terraces and step edges of fully chlorinated stepped silicon surfaces may allow the formation of molecular lines along the reactive step edges.